History, Memory, Performance
XV, 307 p.
Keywords: History, Memory, Performance is an interdisciplinary collection of essays exploring performances of the past in a wide range of trans-national and historical contexts. At its core are contributions from theatre scholars and public historians discussing how historical meaning is shaped through performance.